Occurrence and driving mechanism of antibiotic resistance genes in marine recreational water around Qinhuangdao, China - Han, Ying; Hu, Yikai; Wen, Hexin; Wu, Jiayue; Liu, Yuanwang; Zhang, Yingchao; Wu, Hao (Frontiers in Marine Science, 2022)
Rapid urbanization and other human activities have exacerbated the global human health risks associated with antibiotic resistance genes (ARGs). Swimming in contaminated waters is one of important pathways by which humans can be exposed to ARGs. However, little is currently known about the overall levels of ARGs in recreational waters and the forces driving their occurrence. In this study, we analyzed the ARGs and bacterial communities in water samples taken from five recreational coastal waters (RCWs) and their adjacent estuaries in the Qinhuangdao area of Bohai Bay, China, using high-throughput quantitative PCR and 16S rRNA gene amplicon sequencing technique. The relative abundances of ARGs in RCWs varied greatly, and occurred at levels close to, or even higher than, those in the neighboring estuaries, ranging from 9.4×10-2 to 2.5 copies/16S rRNA gene. A total of 159 different ARGs able to express resistance to almost all antibiotics were detected in all of the water samples. β-lactamase resistance genes (blaTEM gene) were the most abundance of all ARGs. Patterns of ARG occurrence were significantly correlated with those of bacterial communities (Mantel test, P < 0.05). A partial redundancy analysis showed that differences in bacterial communities accounted for 50.3% of the total ARG variations, which was much higher than the sum of the contribution of mobile genetic elements (18.1%) and the other selected environmental factors (8.3%). Principal coordinate analysis based on Bray-Curtis distance revealed the similarities between ARG profiles in the RCWs and in their adjacent estuaries. To our knowledge, this is the first study to report the ARG profiles in RCWs using high throughput qPCR technology. These results implied that it is necessary to develop proper regulations and monitoring strategies of RCWs for reducing risks of ARGs on human health.